Interessante Zeichen für Sprache - Rüdiger Zymner (Recherches Germaniques)
The article discusses several theories of poetry and constructs a new one which reflects upon theories of literary genres, is well informed about the psychology of reception, empirically grounded and epistemically reliable. Thus poetry is (mostly graphic or phonic) representation of language, which functions as a display of linguistic mediality and as a catalyst of aesthetic evidence. In the case of lyrics the mediality of language is indicated above all by attractors of different types, in particular by infractions or interferences on the linguistic level or on that of the information of the lingustic signs (for example meter, rhyme, graphic or phonetic cohesions, rhetorical figures and tropes), which dispose of the potential to generate in the reader a sensual participation or experience.